UJI VIABILITAS, ANTIBAKTERI dan ENZIM HIDROLITIK DARI BAKTERI ASAM LAKTAT (BAL) PETIS - Intan Feby Nurhaliza; Kartika Dewi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The processing of petis commodities begins with fermentation by-products which are then processed with sugar and salt until they have a distinctive aroma. The involvement of probiotic microbes, bioactive chemicals, and micronutrients produced by microbes is very important in fermentation. When food is fermented, lactic acid bacteria play an important role. The development of LAB in fermented foods causes a decrease in pH, which protects food from damage or interference from bacteria that cause spoilage and dangerous infections, including Vibrio spp. In addition, Lactic Acid Bacteria have the potential to produce hydrolase enzymes needed in the manufacture of probiotics. Hydrolase enzymes produced by LAB include cellulase, protease, mannanase, and cellulase. The purpose of this study was to determine the LAB isolate as an antibacterial against the pathogenic bacteria Vibrio sp, to determine the potential of the isolate against the pathogenic bacteria and to determine the potential of LAB as a producer of hydrolase enzymes. The stages carried out in the study consisted of 3 stages, namely refreshing the LAB isolate that had been isolated and preserved. The second stage is testing BAL as a producer of hydrolase enzymes and antibacterial testing on BAL against pathogenic bacteria Vibrio sp. The third stage is data analysis of all data obtained. The target in this study is to be a source of data in the development of the field of biotechnology. This research is one of the priority activities of maritime research in the 2020-2024 UTM RIP with research topics: product diversification, utilization and preservation of marine and fisheries resources.